Penerapan Media Pembelajaran Padlet pada Pembelajaran Matematika - Safiil Maarif; Rinjani Rosa Aprilia; Esty Saraswati Nur Hartiningrum (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research aims to describe the application of Padlet learning media in improving students' mathematics activities and learning outcomes in mathematics induction material for the 2022/2023 academic year. This type of research is classroom action research. The classroom action research design used in this research is a model developed by Kemmis and Mc Taggart. The research was carried out in 2 cycles, the first cycle consisting of 2 meetings and the second cycle consisting of 2 meetings. Researchers collected data by observation and tests. The subjects in this research were 33 class XI-MIPA 2 students at SMAN Bandarkedungmulyo, consisting of 11 male students and 22 female students for the 2022/2023 academic year. Based on the results of research in Cycles I and II, it was seen that student activity increased from 62% with fairly good criteria in cycle I to 86% with very good criteria in cycle II and the average student learning achievement test was 48.75 with a classical percentage of 21 % in cycle I was 80.71 with a classical percentage of 78% in cycle II. In Cycle II, student activities have reached the success criteria and student results have reached ≥76% classically, so by implementing Padlet learning media you can increase student activity and student learning outcomes.